The affect of workplace stressor towards the turnover intentions among hotel employees in Kota Kinabalu - Azuriaty Atang (2010)
This study aims to examine the relationship between the workplace stressor towards the turnover intentions among hotel employees in Kota Kinabalu. The workplace stressors are the role conflict, role ambiguity, intra-group conflict, organizational culture and organizational politics with gender as the moderator. The study took place in star rated hotels in the city of Kota Kinabalu. Data collection were done among operational hotel employees which are from food and beverage department, front office department and house keeping department by handing out 310 sets of questionnaire. The data was then analyzed using the multiple regressions and hierarchical regressions to test the relationship between the workplace stressors and the turnover intentions among the operational hotel employees. Results showed that there was little effect of workplace stressors towards the turnover intentions among the hotel employees with only two independent variables was having a significant relationship. The two variables were intra-group conflict and organizational culture. Meanwhile, gender also moderates the relationship between workplace stressors and the turnover intentions. The research provides a better understanding for employers to understand the workplace stressor effects towards the turnover intentions of their employees especially in the hotel industry. The finding is useful guide to develop strategies to overcome workplace stressors among hotel employees especially those who directly engaged with the guests.